Arthropods community on maize plantation in West Pasaman, West Sumatra, Indonesia - IRFAN SULIANSYAH; SILVIA PERMATA SARI; NOVRI NELLY; HASMIANDY HAMID (Society for Indonesian Biodiversity, 2022)
Abstract. Sari SP, Suliansyah I, Nelly N, Hamid H. 2022. Arthropods community on maize plantation in West Pasaman, West Sumatra, Indonesia. Biodiversitas 23: 3062-3072. Arthropods can be found on the surface of the soil and plant canopy. West Pasaman District is one of the centers of corn production in Indonesia. This study aimed to determine the abundance and the diversity of arthropods in Luhak Nan Duo Sub-district and Kinali Sub-district, West Pasaman District, West Sumatra District, Indonesia. The research was conducted using a purposive sampling technique from October to December 2020. The arthropods sampling was done by two techniques: yellow trap and modified vacuum technique. The identification process was conducted at the Insect Bioecology Laboratory, Faculty of Agriculture, Universitas Andalas, Padang, Indonesia. A total of 5477 arthropods were found in maize plantations in West Pasaman. The arthropods found were classified into two classes, 8 orders, 85 families, and 269 morphospecies. The individual number was dominated by the Insect class, reaching 97.09% (5318), while the Arachnida class was only 2.99% (159). Data were analyzed for the number of species (S), the number of individuals (N), Shannon-Wiener diversity index (H'), and Evenness index of species (J'). Regarding the location, Luhak Nan Duo has a higher number of individuals, Shannon-Wiener diversity index, and Evenness index than Kinali. However, the pattern of arthropod abundance in the two maize cultivation locations in West Pasaman was similar, increasing with the age of the maize plant. However, in general, the diversity values of arthropods in maize cultivation in Luhak Nan Duo and Kinali were more than 3. It means that the West Pasaman is still quite balanced and safe from the risk of damage due to pests because of the highest abundance of arthropods on maize plantations.